Atlas of small animal wound management and reconstructive surgery - Pavletic, Michael M. (John Wiley & Sons, 2018)
A one-stop reference for the surgical treatment of wounds in small animal patients Wound management and reconstructive surgery are among the most challenging and innovative subspecialties of veterinary surgery for the management of traumatic injuries and neoplastic conditions commonly encountered in small animals. Atlas of Small Animal Wound Management and Reconstructive Surgery, Fourth Edition presents detailed procedures for surgical reconstruction and essential information on the principles of wound healing and wound management for dogs and cats. Coverage encompasses the pathophysiology and management of the wide variety of wounds encountered in small animal practice and the most current reconstructive techniques for closing the most challenging defects. This updated edition is presented with additional full color images and now includes color in each illustration, to enhance the reader's understanding of each subject and successful execution of the surgical techniques covered. It imparts new and updated information on a wide variety of topics, including skin and muscle flap techniques, skin fold disorders, facial and nasal reconstructive surgery, foot pad surgery, urogenital reconstructive surgery, and includes a new chapter on reconstructive surgery of the pinna. Provides a key reference for general practitioners, surgeons, surgical residents, veterinary students, and small animal technicians in a single source. Discusses current and new wound management and reconstructive surgical techniques for all body regions, including the face, ear, mouth, eye, nose, trunk, external genitalia, and foot. Contains 35 brand-new plate illustrations, updated and enhanced color plate illustrations and drawings, and additional clinical photographs throughout.